44
$\begingroup$

Let $a$, $b$, $c$, and $d$ be the lengths of the sides of a quadrilateral. Show that $$ab^2(b-c)+bc^2(c-d)+cd^2(d-a)+da^2(a-b)\ge 0 \tag{$\star$}$$

Background: The well known 1983 IMO Problem 6 is the following:

IMO 1983 #6. Let $a$, $b$ and $c$ be the lengths of the sides of a triangle. Prove that $$a^{2}b(a - b) + b^{2}c(b - c) +c^{2}a(c - a)\ge 0. $$

See: here. A lot of people have discussed this problem. So this problem (IMO 1983) has a lot of nice methods.

Now I found for quadrilaterals a similar inequality. Are there some nice methods for inequality $(\star)$?

$\endgroup$
  • 1
    $\begingroup$ Are you certain that the inequality for quadrilateral is correct? $\endgroup$ – zyx Aug 13 '13 at 0:48
  • $\begingroup$ I'm sure, I have use bottem test is ture $\endgroup$ – math110 Aug 13 '13 at 0:50
  • $\begingroup$ What is bottem test? $\endgroup$ – zyx Aug 13 '13 at 0:53
  • 1
    $\begingroup$ old.irgoc.org/Soft/ShowSoft.asp?SoftID=15, This software is the best software validation inequality, developed by several Chinese mathematicians $\endgroup$ – math110 Aug 13 '13 at 1:01
  • 2
    $\begingroup$ Is there an organical way to come up with the one-liner solution? $\endgroup$ – chubakueno Aug 14 '13 at 2:37
14
+50
$\begingroup$

Let $T$ be the function in question: $$ T(a,b,c,d) = a b^2(b-c) + b c^2 (c-d) + c d^2 (d-a) + d a^2 (a - b). $$ We wish to show $T(a,b,c,d)\ge 0$ if $a,b,c,d$ are the sides of a quadrilateral. (Presumably, $a$ is the side opposite $c$ and $b$ is opposite $d$, but it actually doesn't matter to the proof.)

Terminology We introduce the following terminology: If $x_1,x_2,x_3,x_4$ are four real numbers (possibly negative), we say $x_1,x_2,x_3,x_4$ are "quadrilateral" if the following constraint holds: \begin{eqnarray} (*)\ \ \ \ x_1 + x_2 + x_3 + x_4 &\ge& 2 \max\{x_1,x_2,x_3,x_4\}. \end{eqnarray}

We also say that $x_1,x_2,x_3,x_4$ are "linear quadrilateral" if $(*)$ holds with equality.

Obviously, the sides $a,b,c,d$ of a quadrilateral are, well, quadrilateral. If the quadrilateral is degenerate so that its four vertices fall on a line, then its sides are linear quadrilateral.

Basic Idea The basic idea of the proof is to continuously "shrink" the sides $a,b,c,d$ of the quadrilateral by equal amounts $x$ until the quadrilateral collapses and all four of its vertices fall on a line. In other words, $(a-x,b-x,c-x,d-x)$ are linear quadrilateral. In step 3 below, we show this shrinking process decreases $T$, i.e., $T(a-x,b-x,c-x,d-x)$ is decreasing in $x\ge 0$ until $a-x,b-x,c-x,d-x$ are linear quadrilateral. The complexity comes when one realizes that during this shrinking process, one of the sides may collapse through a point and its length become negative (in which case it no longer makes sense to talk about $a-x,b-x,c-x,d-x$ being sides of a quadrilateral). Step 1 handles this "negative" case. Step 2 handles the more natural case in which no side becomes negative during the shrinking process.

Step 1 Suppose $a,b,c,d\ge 0$ are quadrilateral and one of $a,b,c,d$ vanishes. Then $T(a,b,c,d)\ge 0$.

Proof Assume without loss of generality that $a=0$. Then $$ T(0,b,c,d) = b c^3 - b c^2 d + c d^3. $$ Observe \begin{eqnarray} c \ge d &\implies& b c^3 - b c^2 d \ge 0 \implies T(0,b,c,d) \ge 0 \\ d \ge b,c &\implies& c d^3 - b c^2 d \ge 0 \implies T(0,b,c,d) \ge 0. \end{eqnarray} The only other case not covered by these two conditions is $b> d > c$. In this case, we use use the fact that $a,b,c,d$ are quadrilateral to deduce $b\le c+d$. Since $c-d<0$, \begin{eqnarray} T(0,b,c,d) &=& b c^2(c-d) + c d^3 \\ &\ge& c^2 (c+d)(c-d) + c d^3 \\ &=& c^4 - c^2 d^2 + c d^3 \\ &=& c^4 + c d^2 (d - c) \\ &\ge& 0. \end{eqnarray} In any case, $T(0,b,c,d)\ge 0$.

Step 2 Suppose $a,b,c,d\ge 0$ are linear quadrilateral. Then $$ T(a,b,c,d)\ge 0. $$

Proof Without loss of generality, suppose $d=\max\{a,b,c,d\}$, so $d=a+b+c$.

By direct computation, \begin{eqnarray} T(a,b,c,a+b+c) &=& a^4 - a^2 b^2 + a b^3 + a^3 c + a b^2 c + b^3 c + a^2 c^2 + 3 a b c^2 \\ & & \ + 2 b^2 c^2 + 2 a c^3 + 3 b c^3 + c^4. \end{eqnarray}

Luckily, the only summand that can possibly be negative is $-a^2 b^2$. Observe \begin{eqnarray} a\ge b &\implies& a^4 - a^2 b^2 \ge 0 \\ a\le b &\implies& a b^3 - a^2 b^2 \ge 0. \end{eqnarray} Thus, $$ T(a,b,c,a+b+c) \ge a^4 + a b^3 - a^2 b^2 \ge 0. $$

Step 3 Suppose $a,b,c,d$ are linear quadrilateral and not all equal. Suppose the sum of any two of $a,b,c,d$ is non-negative. Then for $x\ge 0$, the mapping $$ x \mapsto T(a+x,b+x,c+x,d+x) $$ is strictly increasing in $x$.

Proof

Without loss of generality, let $d=\max\{a,b,c,d\}$. Since $a,b,c,d$ are linear quadrilateral, $$ d = a + b + c. $$

Direct computation shows $$ T(a+x,b+x,c+x,d+x) = T(a,b,c,d) + A x + B x^2 $$ where \begin{eqnarray} A &=& a^3 - a^2 b + 2 a b^2 + b^3 - 2 a b c - b^2 c + 2 b c^2 + c^3 \\ & & \ + 2 a^2 d - 2 a b d - 2 a c d - 2 b c d - c^2 d - a d^2 + 2 c d^2 + d^3. \end{eqnarray} and \begin{eqnarray} B &=& 2 a (a - b) + a (b - c) + 2 b (b - c) + b (c - d) \\ & & \ + 2 c (c - d) + (a - b) d + c (-a + d) + 2 d (-a + d) \\ &=& (a-c)^2 + (b-d)^2 + \frac{1}{2}(a-b)^2 + \frac{1}{2}(a-d)^2 + \frac{1}{2}(b-c)^2 + \frac{1}{2}(c-d)^2. \end{eqnarray} Clearly, $B>0$ because $a,b,c,d$ are not all the same.

Now substitute $d=a+b+c$ in the expression for $A$ and simplify: $$ A = 3 a^3 + 2 a b^2 + 2 b^3 + 3 a^2 c + 2 b^2 c + 3 a c^2 + 6 b c^2 + 3 c^3. $$

Suppose $a<0$. Since the sum of any two of $a,b,c,d$ is non-negative, $b,c,d\ge |a|$. Observe \begin{eqnarray} A &=& 3 a^3 + 2 a b^2 + 2 b^3 + 3 a^2 c + 2 b^2 c + 3 a c^2 + 6 b c^2 + 3 c^3 \\ &=& (3 a^3 + 3a^2 c) + (2 a b^2 + 2 b^3) + (3 a c^2 + 3 c^3) + 2 b^2 c + 6 b c^2 \\ &\ge& 0. \end{eqnarray} (All the quantities in parentheses are non-negative.)

Suppose $b<0$. Because the sum of any two of $a,b,c,d$ is non-negative, $a,c,d\ge |b|$. We have \begin{eqnarray} A &=& 3 a^3 + 2 a b^2 + 2 b^3 + 3 a^2 c + 2 b^2 c + 3 a c^2 + 6 b c^2 + 3 c^3 \\ &=& (2 b^3 + 2 a b^2) + (6 b c^2 + 3 c^3 + 3 a c^2) + 3 a^3 + 3 a^2 c + 2 b^2 c \\ &\ge& 0. \end{eqnarray}

Finally, suppose $c<0$. Then $a,b,d\ge |c|$ and \begin{eqnarray} A &=& 3 a^3 + 2 a b^2 + 2 b^3 + 3 a^2 c + 2 b^2 c + 3 a c^2 + 6 b c^2 + 3 c^3 \\ &=& (3 a^2 c + 3 a^3) + (2 b^2 c + 2 a b^2)+ (3 c^3 + 3 a c^2) + 6 b c^2 + 2 b^3 \\ &\ge& 0. \end{eqnarray}

Since $B>0$ and $A\ge 0$, the result follows.

Step 4 Suppose $a,b,c,d\ge 0$ are quadrilateral and not all the same. Then $T(a,b,c,d) > 0$.

Proof Make the following definitions: \begin{eqnarray} x_0 &=& \frac{1}{2}(a+b+c+d - 2\max\{a,b,c,d\}) \\ A &=& a - x_0 \\ B &=& b - x_0 \\ C &=& c - x_0 \\ D &=& d - x_0. \end{eqnarray}

It is easy to see $A,B,C,D$ are linear quadrilateral. Furthermore, the sum of any two of $A,B,C,D$ is non-negative. For example, \begin{eqnarray} A+B &=& a + b - 2 x_0 \\ &=& 2\max\{a,b,c,d\} - c - d \\ &\ge& 0. \end{eqnarray} All the other cases are just as easy.

Consider the function $f:[0,\infty)\to\mathbb{R}$ defined by $$ f(x) = T(A+x,B+x,C+x,D+x). $$ It follows from step 3 that $f$ is strictly increasing.

Since $a,b,c,d$ are quadrilateral, $x_0\ge 0$, so $T(a,b,c,d) = f(x_0) \ge f(0)$. If $A,B,C,D$ are all non-negative, then $f(0)\ge 0$ by step 2 and we are done.

Let $m=\min\{a,b,c,d\}$ and suppose one of $A,B,C,D$ is negative, so $m < x_0$. Then $T(a,b,c,d) = f(x_0) > f(m)$. But by step 1, $f(m)\ge 0$ and we are done.

$\endgroup$
  • $\begingroup$ Your solution uses the same basic idea as mine, but don't you think it is easier to use AM-GM as I did to finish it after that? $\endgroup$ – user21820 Dec 8 '13 at 9:18
  • $\begingroup$ @user21820 You only cover what I call "Step 2", which is just a couple lines of my proof. You assert that decreasing $(a,b,c,d)$ simultaneously by $t$ reduces the desired expression, but you don't prove this. (I do in my Steps 3 and 4.) Furthermore, note that when you perform the reduction, at least one of the sides can actually become negative. (Take $0,100,100,100$, for example. In this case, one reduces by 50, making the shortest side go negative.) One needs to think about that possibility. $\endgroup$ – Will Nelson Dec 8 '13 at 9:41
  • $\begingroup$ @user21820 It's not anywhere close to obvious that the reduction causes $T(a,b,c,d)$ to decrease. It's a ton of algebra. I proved that in my Steps 3 and 4. If you believe it's trivial, you might want to stare at my Step 4, in particular, and see if there's much unwarranted complexity. I don't see it. Also, it's not a problem of a side going to $0$, it's a problem of a side going negative, as in the $0,100,100,100$ case, which reduces to $-50,50,50,50$. If you allow that, you'll need to prove results when one of the sides might be negative, which can obviously introduce a lot more trickiness. $\endgroup$ – Will Nelson Dec 8 '13 at 10:00
  • $\begingroup$ You're right that I didn't check that the reduction works. As for the negative case, I thought we can decrease until either one side is zero or the quadrilateral shrinks to a line? $\endgroup$ – user21820 Dec 8 '13 at 10:01
  • 2
    $\begingroup$ @user21820 I wouldn't delete it if I were you. You've got lots of upvotes. There are some holes (some large) in the answer, but it's good as far as it goes. I am beginning to wonder how closely and carefully people read answers here, though! $\endgroup$ – Will Nelson Dec 8 '13 at 23:00
4
$\begingroup$

WLOG $a = \max(a,b,c,d)$

Let $t = \frac{1}{2} (b+c+d-a) \ge 0$ because $a$,$b$,$c$,$d$ are sides of a quadrilateral

Then decreasing $(a,b,c,d)$ simultaneously by $t$ reduces the desired expression

And $a-t = (b-t)+(c-t)+(d-t)$

Thus it suffices to minimize the expression when $a=b+c+d$, which reduces to: $ \begin{align} &(b+c+d) b^2 (b-c) + b c^2 (c-d) - c d^2 (b+c) + d (b+c+d)^2 (c+d) \\ & = \left( b^4 - b^2 c^2 + b^3 d - b^2 c d \right) + \left( b c^3 - b c^2 d \right) - c d^2 (b+c) + d (b+c+d) (b+c+d) (c+d) \\ & \ge \left( b^4 - b^2 c^2 + b^3 d - b^2 c d \right) + \left( b c^3 - b c^2 d \right) - c d^2 (b+c) + \Big( d (b+c) d c + d (b+c) (b+c) c \Big) \\ & \ge \left( b^4 - b^2 c^2 + b^3 d - b^2 c d \right) + \left( b c^3 - b c^2 d \right) + b (b+c) c d \\ & \ge b^4 - b^2 c^2 + b c^3 \\ & \ge 0 \quad\text{because} \quad \frac{1}{3} ( b^4 + 2 b c^3 ) \ge b^2 c^2 \quad \text{by AM-GM} \end{align} $

$\endgroup$
  • 1
    $\begingroup$ So just to be clear: this answer asserts but does not prove that decreasing $a,b,c,d$ simultaneously reduces the desired expression. (This is non-trivial. It's step 3 of my proof.) Furthermore, this reduction can result in negative lengths, which adds a lot of complexity. See steps 1 and 4 of my answer. $\endgroup$ – Will Nelson Dec 8 '13 at 20:50
1
$\begingroup$

WLOG, assume that $a = \max(a, b, c, d)$. Let $x = a- b, \ y = a-c, \ z = a-d$. Then $x, y, z \ge 0$. Let $w = b+c+d - a$. Then $w > 0$ since $a, b, c, d$ are the sides of a quadrilateral.

The inequality is written as $$\frac{1}{4}Aw^2 + \frac{1}{4}Bw + \frac{1}{4}C \ge 0$$ where \begin{align} A &= 2\, x^2 - x\, y - 2\, x\, z + 2\, y^2 - y\, z + 2\, z^2,\\ B &= 2\, x^3 + 4\, x^2\, y - 2\, x\, y^2 - 4\, x\, y\, z + 2\, y^3 + 4\, y^2\, z - 2\, y\, z^2 + 2\, z^3,\\ C &= (x+3z)y^3 - 4xzy^2 + (3x^3+3x^2z-3xz^2+z^3)y. \end{align} It suffices to prove that $A, B, C \ge 0$. We have \begin{align} A = (x^2 - xy + y^2) + (y^2 - yz + z^2) + (z^2 - 2zx + x^2) \ge 0 \end{align} and \begin{align} B &= 2x^3 + 3x^2y + (x^2y - 2xy^2 + y^3) - 2(2xz)y + y^3 + 3y^2z + z^3 + (y^2z - 2yz^2 + z^3)\nonumber\\ &\ge 2x^3 + 3x^2y - 2(x^2+z^2)y + y^3 + 3y^2z + z^3\nonumber\\ &= 2x^3 + x^2y + y^3 + 2y^2z + (y^2z + z^3 - 2yz^2)\nonumber\\ &\ge 0. \end{align} And $C\ge 0$ follows from \begin{align} &4(x+3z)(3x^3+3x^2z-3xz^2+z^3) - (4zx)^2\nonumber\\ =\ & 12x^4+48x^3z+8x^2z^2-32xz^3+12z^4\nonumber\\ =\ & (12x^4 - 16x^3z + 24x^2z^2) + 64x^3z - 16x^2z^2 - 32xz^3 + 12z^4\\ \ge \ & 64x^3z - 16x^2z^2 - 32xz^3 + 12z^4 \nonumber \\ = \ & 4z(4x+3z)(2x-z)^2\nonumber\\ \ge \ &0. \end{align} We are done.

$\endgroup$
0
$\begingroup$

use the ptolemy inequality !

$ab^2(b-c)+bc^2(c-d)+cd^2(d-a)+da^2(a-b)\ge 0$$\Longrightarrow$

$2(ab^3+bc^3+cd^3+da^3)\ge$$b^2\cdot{a}(b+c)+c^2\cdot{b}(c+d)+d^2\cdot{c}(a+d)+a^2\cdot{d}(a+b)$$\Longrightarrow$

$2(ab^3+bc^3+cd^3+da^3)\ge$$b^2\cdot{a}l_{1}+c^2\cdot{b}l_{2}+d^2\cdot{c}l_{1}+a^2\cdot{d}l_{2}$$\Longrightarrow$

$8abcd\ge$$b^2\cdot{a}l_{1}+c^2\cdot{b}l_{2}+d^2\cdot{c}l_{1}+a^2\cdot{d}l_{2}$$\Longrightarrow$

$8\ge$$bl_{1}/cd+cl_{2}/ad+dl_{1}/ab+al_{2}/bc$

if $bl_{1}/cd,cl_{2}/ad,dl_{1}/ab,al_{2}/bc\ge2$

then, $l_{1}l_{2}abcd\ge bc\cdot(cd)^2+ad\cdot(ab)^2+ab\cdot(bc)^2+cd\cdot(ad)^2$

$\Longrightarrow$$ac+bd\ge 4\sqrt{abcd}$$\Longrightarrow$$l_{1}l_{2}\ge ac+bd$

which contradict with the ptolemy inequality !

$\endgroup$
0
$\begingroup$

Let $\;$ $LHS=f(a,b,c,d)$. Note that $f(a,b,c,d)>f(a-k,b-k,c-k,d-k)$ for $0<k\le\min\{a,b,c,d\}$. So, WLOG we can take $d=0$ to prove the inequality. In that case we should show $ab^2(b-c)+bc^3\ge0$. If $b\ge c$ obviously we are done. For $c\ge b \ge a$ and $c\ge a \ge b$ cases arranging the inequality shows us $ab^3+bc(c^2-ab)\ge0$. Now, $a\ge c \ge b$ case remained. We will use the inequality $a\ge c$. Let's arrange the inequality again. Then, $ab^2(b-c)+bc^3\ge cb^2(b-c)+bc^3=b^3c-b^2c^2+bc^3\ge0$ $\;$ (by AM-GM $b^3c+bc^3\ge 2b^2c^2$ )

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.